Association between Antenatal Visit Compliance and Mode of Delivery in Low-Risk Pregnancies - Umm E Aiman Saleem, Uzma Zaman, Dilruba, Aiman Kaleem, Neelum Roshan, Sunaina Rauf (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The current paper aims at exploring the association between the mode of delivery and antenatal visit compliance during the low risk pregnancies. It also explores the connection between the planned visits to the antenatal care and compliance with that planned visits to the antenatal care and the outcome delivery; that is, the possibility of delivery through the vagina or a caesarean section delivery. Methods: The approach was quantitative, observational and data were analyzed with records of the low-risk pregnant women who had visited the antenatal care in a local healthcare facility. The rate and timing (weeks of pregnancy when the antenatal visits took place) of the antenatal visits and mode of delivery (vaginal birth, elective or emergency caesarean section) were identified. The association between the percentage of attendance of antenatal visits and the outcomes of delivery was statistically studied through chi-square and regressions. It was done on a sample of 500 low-risk pregnancies and at the time of examination, the variables such as the maternal age, socioeconomic status, and BMI were controlled. Results: They found out that the women who adhered to the suggested antenatal visit schedules would have more opportunities of a vaginal birth and the amount of elective caesarean delivery had greatly reduced. Compliance with the timely and routine prenatal check-ups has been reported to not only lead to an improved maternal and fetal outcome but also non-compliance increased the likelihood of emergency caesarean sections. The statistical result revealed that a strong association existed between regular antenatal visits and good child birth outcomes. Conclusion: The research reveals that the value of antenatal visits in the identification of delivery mode during the low-risk pregnancies. It can enhance better maternal and fetal outcomes by improving compliance to antenatal care that will avoid unnecessary caesarean section and delivering a better experience on deliveries. Healthcare policies ought to concentrate on making available to all pregnant women and making them go through with the scheduled antenatal check ups in an attempt to maximize the outcomes of their pregnancy. Keywords: Antenatal Visit Compliance, Low-Risk Pregnancies, maternal care